Atypical thymic carcinoid associated with rapidly progressive symptoms of Cushing's syndrome in a child - Abe, Takatoshi; Sakai, Seisho; Nomura, Kozo; Mizushima, Honami; Hayashi, Kentaro; Sakai, Yuta; Noguchi, Kazuhiro; Fujiki, Toshihiro; Kuroda, Rie; Ikawa, Yasuhiro; Saito, Daisuke; Matsumoto, Isao (Journal of pediatric surgery case reports, 2022)
Atypical thymic carcinoid in children is rare and its prognosis principally depends on the completeness of the surgical resection. We report a case of atypical thymic carcinoid with lymph node metastasis that had not been identified prior to surgery. An 8-year-old boy was referred because of Cushing's syndrome and a worsening of his symptom, which included facial edema, fatigue, and headache, over 3 weeks. Blood testing revealed high plasma cortisol and adrenocorticotropic hormone (ACTH), and chest computed tomography demonstrated two tumors in his anterior mediastinum, but no findings suggestive of lymph node metastasis. We suspected the presence of an ACTH-producing thymic carcinoid tumor; therefore, the patient underwent total thymectomy and dissection of his anterior mediastinal and bilateral deep cervical lymph nodes. Histopathological examination revealed an atypical carcinoid tumor and left cervical lymph node metastasis. The patients' plasma cortisol and ACTH concentrations decreased after surgery, and he was further treated with radiotherapy and combination chemotherapy. Thus, it is possible that the development of symptoms may indicate more rapid progression of atypical thymic carcinoid, and deep cervical lymphadenectomy is necessary for its complete resection.